2023
DOI: 10.3390/app132212514
|View full text |Cite
|
Sign up to set email alerts
|

A Thorough Investigation of the Dynamic Properties of Granite under Cyclic Loading

Xiaobin Ding,
Junxing Zhao,
Yaojun Dong
et al.

Abstract: We propose a novel inverse analysis method that utilizes shockwaves to detect the operational condition of tested rock. To achieve this back analysis, an in-depth investigation of the dynamic properties of granite specimens was conducted. The dynamic properties of the granite specimens were investigated using a triaxial cyclic loading machine, under different confining pressures, loading frequencies, stress amplitudes, and numbers of cycles, and a dynamic response model was constructed from the test data. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…During this phase, the internal microcracks and fatigue damage in the granite progressively accumulate with each cycle, resulting in increased plastic deformation and, consequently, a decline in elastic stiffness. Several studies have revealed that an augmentation in the upper load limit leads to a decline in the elastic stiffness of the tested specimens [31,53]. This occurrence can be ascribed to the acceleration of crack development and the consequent premature initiation of the elastic stiffness degradation phase caused by the heightened upper load limit.…”
Section: Evolution Of Elastic Stiffnessmentioning
confidence: 99%
See 1 more Smart Citation
“…During this phase, the internal microcracks and fatigue damage in the granite progressively accumulate with each cycle, resulting in increased plastic deformation and, consequently, a decline in elastic stiffness. Several studies have revealed that an augmentation in the upper load limit leads to a decline in the elastic stiffness of the tested specimens [31,53]. This occurrence can be ascribed to the acceleration of crack development and the consequent premature initiation of the elastic stiffness degradation phase caused by the heightened upper load limit.…”
Section: Evolution Of Elastic Stiffnessmentioning
confidence: 99%
“…The results indicated that the fracture toughness of the specimens experiences a noticeable decrease when subjected to cyclic loading. Regarding cyclic loading frequency, Zhu et al [30] and Ding et al [31] examined the connection between cyclic loading frequency and crack propagation. Their findings demonstrated that at higher frequencies, such as 1 Hz, cracks exhibit rapid growth in terms of length, number, and width.…”
Section: Introductionmentioning
confidence: 99%